Discordance in exclusive breastfeeding between maternal recall and deuterium dose-to-mother technique during the first 6 months of infants: A multi-country study in Asia - Winichagoon P. (2023)
Purpose: This study aimed to assess the agreement in EBF between maternal recall and the dose-to-mother (DTM) technique. Methods: Indonesia, Malaysia, Mongolia, Pakistan, Sri Lanka, Thailand, and Vietnam participated in the study. A total of 207 and 118 mother-infant pairs were assessed at 3 and 6 months of child’s age. Using a standardized questionnaire, mothers were asked to recall child feeding during the previous 24 h, at 3 and 6 months. Those recalled to be EBF proceeded to be assessed using DTM technique. Non-milk oral intake (NMOI) cutoff of 86.6 g/d was used to classify EBF. Results: According to DTM, 66% of infants were EBF at 3 months, while only 22% were EBF at 6 months. At 3 months, the overall % agreement between maternal recall and DTM method was 68%, kappa 0.06 (95% CI: 0.07–0.20), and at 6 months, the % agreement was only 21%, kappa -0.031 (95% CI -0.168 to 0.107). Human milk intakes were similar at 3 months and 6 months when expressed as g/d, but decreased when expressed as g/kg/d, with a large variation within and between countries; Pakistan being the lowest. Conclusion: This study showed there were declining levels of EBF from 3 to 6 months in the participating countries from Asia and the agreement between maternal recall and DTM technique to classify EBF was low. To ensure that the DTM technique can be more widely used in evaluating breastfeeding promotion programs, consensus on the appropriate NMOI cutoff and simplification of the DTM protocol is necessary.